A neuroscience-based approach to the assessment of sexual behavior in animals - Tekin, Samet; Akgün, Elif Ece; Ömür, Ali Doğan (Frontiers in Veterinary Science, 2023)
Sexual behavior in animals is important in ensuring the continuity of the generation. These behaviors differ in animal species. Sexual behaviors are shaped under the control of the reproductive system. Physiological stimuli produced by the reproductive system find their counterparts in the organism as reproductive activity. Reproductive activity display a critical role by transferring on the genetic heritage of organisms to the next generations. This activity, which is built on delicate balances, is associated with many systems in the organism. Nervous system, hormonal system, and circulatory system are the main ones. The regular formation of the reproductive activity in species is due to the effect of various factors. In domestic mammals, the reproductive activity is regulated by hormones secreted from brain and endocrine glands. Many hormones have duties in terms of the sustainability of reproductive activity. GnRH is the main hormone responsible for initiating this reproductive activity. Gonadotropin-releasing hormone (GnRH), which is a small molecule peptide from certain nerve cells in the nucleus infundibularis region of the hypothalamus and consists of different amino acids, is secreted under the influence of smell, temperature, light, and physical stimulation. Besides, GnRH release is controlled by various neurotransmitters (adrenaline, noradrenaline, dopamine, acetylcholine, serotonin). On the other hand, various genetic factors in secretory glands, gonadal cells, reproductive tissues can lead to significant changes on reproductive activity through specific molecular pathways and mechanisms.